Am nevoie de ajutor la acest exercițiu !
Anexe:
Răspunsuri la întrebare
Răspuns de
0
a
2 − b
2 = (a + b)(a − b)
36=4(a+b)
a+b=36/4
a+b=9
36=4(a+b)
a+b=36/4
a+b=9
Răspuns de
0
a² - b² = 36 ⇒ (a - b)(a + b) = 36 (1)
a - b = 4 (2)
Din relațiile (1), (2) ⇒ 4·(a + b) = 36 ⇒ a + b = 36:4 ⇒ a + b = 9.
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă